Proceedings 2007 IEEE International Conference on Robotics and Automation 2007
DOI: 10.1109/robot.2007.363056
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a New Steady-Hand Manipulator for Retinal Surgery

Abstract: Abstract-This paper describes the development and initial testing of a new and optimized version of a steady-hand manipulator for retinal microsurgery. In the steady-hand paradigm, the surgeon and the robot share control of a tool attached to the robot through a force sensor. The robot controller senses forces exerted by the operator on the tool and uses this information in various control modes to provide smooth, tremor-free, precise positional control and force scaling. The steady-hand manipulator reported h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 16 publications
(15 reference statements)
0
109
0
Order By: Relevance
“…Leng et al [13] reported that the chorioallantoic membrane (CAM) of a 12 days old chicken embryo is a good test model system for retinal surgery since at around this age the secondary veins on the surface of the CAM are of a size that closely matches the size of the veins on the human retina. A previously collected video recording of a CAM vein cannulation procedure (under IRB approval, [14]) was used to asses the tracking algorithm. Under these conditions we noticed a tracking processing speed of 31-33 FPS.…”
Section: Resultsmentioning
confidence: 99%
“…Leng et al [13] reported that the chorioallantoic membrane (CAM) of a 12 days old chicken embryo is a good test model system for retinal surgery since at around this age the secondary veins on the surface of the CAM are of a size that closely matches the size of the veins on the human retina. A previously collected video recording of a CAM vein cannulation procedure (under IRB approval, [14]) was used to asses the tracking algorithm. Under these conditions we noticed a tracking processing speed of 31-33 FPS.…”
Section: Resultsmentioning
confidence: 99%
“…16 Another adaptation, the Microhand (consisting of four fingers), was designed to mimic a human hand while being pneumatically controlled, allowing titration of grasping force. 17 The steady-hand manipulator 18,19 and Micron 20 were two independently developed instruments capable of tremor filtration for microsurgical procedures. Japanese collaborators recently created a prototype robotic system designed to aid in vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The position resolution is 1µm and measured repeatability is about ± 1 µm for range of motion required for this experiment (<2mm). This robot was chosen for experimental convenience, and would be replaced in actual practice by a system similar to [9][10]. The robot is interfaced to a PC workstation through a commercial motion controller (Galil DMC 1886).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to alternative approaches, CP-OCT is simple, robust, and affordable [8], and also permits an extremely compact tool design. This "A-mode" sensing capability can either be used with conventional free-hand instruments or (as here) can be combined with a robotic microsurgery platform such as the JHU EyeRobot [9] or the CMU Micron [10]. When integrated with a robot, this instrument may be scanned to produce images of the local anatomy or integrated in various ways to the control the robot.…”
Section: Introductionmentioning
confidence: 99%